FIGURATIVE LANGUAGE USED IN ARIANA GRANDE ALBUM ENTITLED “ETERNAL SUNSHINE” 2024 - Idris, Vinna; Sunra, La; Affandi, Akhmad (State University of Makassar, 2025)
This study aims to analyze the types of figurative language in the song album “Eternal Sunshine” by Ariana Grande using Perrine's (1982) theory. The analysis method used refers to the semantic approach by considering Leech's (1981) theory to explore the meaning in various types of figurative language. The research data was obtained from the extraction of 29 figurative language sentences consisting of metaphor (2), simile (6), personification (1), hyperbole (11), apostrophe (1), understatement (2), irony (4), and metonymy (2). The analysis also identified two main categories of meaning that are frequently used, namely associative meaning and connotative meaning. This research provides a deep insight into how Ariana Grande uses different types of figurative language to enrich the reader's experience and convey a profound message in “Eternal Sunshine.” Our analysis reveals the album's distinctive use of figurative language, characterized by the prominence of metaphor and hyperbole. While previous research on albums such as “Thank you, next” by DeniArnita Hulu and “Runaway” by Putu Yoga found similes and metaphors to be the dominant forms of figurative language, our study highlights the dominance of hyperbole in “Eternal Sunshine.” In addition, the novel shows a balanced variety of figurative techniques and a clear distinction between associative and connotative meanings. This research is expected to contribute to the understanding of literature and the use of figurative language in modern literary works.Keywords: Figurative Language; Perrine; Leech; Song; Eternal Sunshine